Benign tumours of women genital tract with clinical malignancy - Kowalczyk-Amico, Katarzyna; Szubert, Maria; Hendzel, Katarzyna; Suzin, Jacek (Menopause Review/Przegląd Menopauzalny, 2009)
Benign tumours of the women genital tract are very common. Objective: to present a few cases of patients with histologically benign lesions of uterus and adnexa, who developed features of local and clinical malignancy of the tumour in postoperative period. Material and methods: A retrospective analysis of 5 patients operated due to genital tract tumours in I Department of Obstetrics and Gynaecology, Medical University Łodz, was conducted. The patients included in the study fulfilled the following criteria: tumours were evaluated as ”benign” both in intraoperative as well as in postoperative histopathological examination, the patients were followed-up in our out-patients room, there were symptoms of tumour reccurence in postoperative period. Results: At the primary operation an ovarian tumour of cystadenoma mucinosum type was detected in three patients. Other two patients presented benign mass of uterine origin: angioleiomyoma and benign metastasizing leiomyoma. All conducted laparotomies were complicated with abnormal bleeding, mucinous masses from ruptured tumours, massive adhaesions in the peritoneal cavity, changes in the anatomy of the pelvis caused by size of the lesions. In all of the operated patients a reccurence of the lesion was diagnosed in the postoperative follow-up. Conclusions: Clinical malignancy of the histologically benign tumour of the genital tract can be described as an ability for local recurrence with symptoms from digestive and urinary tract caused by ”mass-efect”, potential metastastic spread to other organs with a consequence in their failure, deterioration in physical condition due to tumour related anemia, lack of proteins, cachexia. Every patient operated on benign genital tract lesions should be closely followed-up to diagnose early reccurence of the tumour.